Effect of Company Firms size, Debt to Total Asset, and Return on asset on Dividend Payout Ratio (Emprirical Study of Coal Sector Companies Listed on the Indonesia Stock Exchange in 2016-2020: Pengaruh Ukuran Perusahaan, Debt to Total Assets, dan Return on Assets terhadap Dividend Payout Ratio (Studi Empiris Perusahaan Sektor Batubara yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2020 - Bambang prasetyo; Ramel Yanuarta (Universitas Negeri Padang, 2023)
This study aims to examine the impact of company size variables, Debt to total assets (DTTA), and Return on assets (ROA) on dividend payout ratios in coal companies listed on the Indonesia Stock Exchange during the 2016-2020 period. This type of research is quantitative. The research sample consisted of 23 companies selected using purposive sampling method. Multiple linear regression analysis was used to determine the effect of the independent variables on the dependent variable. This study uses SPSS 23 data processing. The results of this study for the variables Firm Size, Debt to total assets, and Return on asset ratio have a significant effect on Dividend payout in coal companies listed on the Indonesia Stock Exchange.